DJ-1 promotes osteosarcoma progression through activating CDK4/RB/E2F1 signaling pathway - Han, Zhitao; Wang, Lining; Wang, Dongshuo; Zhang, Luosheng; Bi, Yifeng; Zheng, Xinlei; Liu, Weibo; Bai, Guangjian; Wang, Zhenhua; Wan, Wei; Ma, Yong; Cai, Xiaopan; et al. (Frontiers in Oncology, 2022)
Osteosarcoma (OS) is a primary malignant tumor of the bone characterized by poor prognosis due to chemotherapy resistance and high recurrence rates. DJ-1 (PARK7) is known as an oncogene and its abnormal expression is related to the poor prognosis of various types of malignant tumors. It was found in this study that upregulated expression of DJ-1 was closely correlated with the prognosis of OS patients by promoting the proliferation, migration and chemotherapy resistance of OS cells in vitro through regulating the activity of CDK4 but not through the oxidation mechanism or AKT pathway. The combination of DJ-1 and CDK4 promoted RB phosphorylation, leading to the dissociation of E2F1 into the nucleus to regulate the expression of cell cycle-related genes. The tumor xenograft mouse model demonstrated that DJ-1 knockout suppressed tumor growth in vivo. All these findings indicate that DJ-1 can affect the occurrence and progression of OS by regulating the CDK/RB/E2F1axis, suggesting a novel therapeutic opportunity for OS patients.